Insulin Resistance and Ovulatory Dysfunction in Polycystic Ovary Syndrome: A Study Using the Muharam Criteria at RSUD Banten - Arya Ady Nugroho; Novitrian Eka Putra (PT Dexa Medica, 2026)
Background: Polycystic ovary syndrome (PCOS) is a leading cause of anovulatory infertility. Insulin resistance (IR) plays a central role in its pathophysiology, contributing to hyperandrogenism and follicular dysfunction. The Muharam criteria, defined as the ratio of fasting plasma glucose to fasting insulin, represents a simple and practical method for assessing IR,particularly in resource-limited settings. This study investigates the correlation between IR, as measured by the Muharam criteria, and ovulatory dysfunction in patients with PCOS at RSUD Banten. Methods: This cross-sectional study included21 women aged 18–40 years diagnosed with PCOS, according to the Rotterdam 2003 criteria. Participants were recruited from the Fertility and Endocrinology Clinic RSUD Banten between January and July 2025. Fasting plasma glucose andinsulin levels were measured, and the value of Muharam criteria was calculated, with cut-off value of <10.1 indicating IR. Ovulatory dysfunction was assessed based on menstrual history and ultrasonographic findings. The correlation betweenIR and ovulatory dysfunction was analyzed using the Spearman test (p<0.05). Results: Among all participants, twelve (57.1%) subjects had a Muharam criteria value of <10.1, indicating IR. Ovulatory dysfunction was present in 16 (76.2%)subjects. The mean Muharam criteria was significantly lower in participants with ovulatory dysfunction compared to those with normal ovulation (8.6 ± 2.3 vs. 11.8 ± 2.5). A significant negative correlation was found between the Muharam criteria and ovulatory dysfunction (ρ = -0.45, p=0.031). Furthermore, insulin resistance was found to increase the risk of ovulatorydysfunction by 3.1 times (odds ratio [OR] = 3.1; 95% CI: 1.05–9.2). Conclusion: The Muharam criteria represents a useful tool for assessing insulin resistance in PCOS patients. A significant correlation was found between insulin resistance and ovulatory dysfunction. Given its simplicity and cost-effectiveness, the Muharam criteria may serve as a valuable screening method, particularly in resource-limited settings.